Impact of the type of SERPINC1 mutation and subtype of antithrombin deficiency on the thrombotic phenotype in hereditary antithrombin deficiency - Luxembourg, Beate; Pavlova, Anna; Geisen, Christof; Spannagl, Michael; Bergmann, Frauke; Krause, Manuela; Alesci, Sonja; Seifried, Erhard; Lindhoff-Last, Edelgard (Thrombosis and Haemostasis, 2014)
Mutations in the antithrombin (AT) gene can impair the capacity of AT to bind heparin (AT deficiency type IIHBS), its target proteases such as thrombin (type IIRS), or both (type IIPE). Type II AT deficiencies are almost exclusively caused by missense mutations, whereas type I AT deficiency can originate from missense or null mutations. In a retrospective cohort study, we investigated the impact of the type of mutation and type of AT deficiency on the manifestation of thromboembolic events in 377 patients with hereditary AT deficiencies (133 from our own cohort, 244 reported in the literature). Carriers of missense mutations showed a lower risk of venous thromboembolism (VTE) than those of null mutations (adjusted hazard ratio [HR] 0.39, 95% confidence interval [CI] 0.27–0.58, p<0.001), and the risk of VTE was significantly decreased among patients with type IIHBS AT deficiency compared to patients with other types of AT deficiency (HR 0.23, 95%CI 0.13–0.41, p<0.001). The risk of pulmonary embolism complicating deep-vein thrombosis was lower in all type II AT deficiencies compared to type I AT deficiency (relative risk 0.69, 95%CI 0.56–0.84). By contrast, the risk of arterial thromboembolism tended to be higher in carriers of missense mutations than in those with null mutations (HR 6.08-fold, 95%CI 0.74–49.81, p=0.093) and was 5.9-fold increased (95%CI 1.22–28.62, p=0.028) in type IIHBS versus other types of AT deficiency. Our data indicate that the type of inherited AT defect modulates not only the risk of thromboembolism but also the localisation and encourage further studies to unravel this phenomenon.
Keywords: Antithrombin deficiency; SERPINC1; mutation; venous thromboembolism; arterial thromboembolism